THE IMPACT OF INFORMATION ASYMMETRY, MORAL HAZARD AND THE STRUCTURE OF FUNDING ON CORPORATE U.S. DOLLARS LOAN PRICING: THE EMPIRICAL STUDY IN INDONESIA THE PERIOD 1990-1997 - Deddy Marciano; Suad Husnan (Research Center and Case Clearing House PPM School of Management, 2014)
This study aims to answer the question: